Pengaruh Model Inquiri Terbimbing Dipadu dengan Metode Proyek terhadap Kemampuan Berpikir Kreatif dan Hasil Belajar Kognitif Siswa - Kalsum, Kalsum; Fatmawati, Baiq; Marhamah, Marhamah (Bioscientist : Jurnal Ilmiah Biologi, 2022)
The use of guided project and inquiry methods theoretically encourages students to think creatively to solve problems in the real environment, train students to work together in groups, and produce products that are meaningful to students. This study aims to determine (1) the difference in the effect of the project method and guided inquiry on creative thinking skills and students' cognitive learning outcomes. (2) the effect of the guided inquiry and project method on students' creative thinking abilities (3) the effect of the guided inquiry and project method on students' cognitive learning outcomes (4) the effect of the project method on students' creative thinking abilities (5) the effect of project methods on students' cognitive learning outcomes (6) the influence of the guided inquiry method on students' creative thinking skills. (7) the effect of the guided inquiry method on students' cognitive learning outcomes. on recycled class V waste materials at SD Negeri 3 dasan lekong. Academic year 2020/2021. The type of this research is Quasi Experiment Control Group Experiment Posttest Only Design. The population is all students of class V, totaling 48 students. Which consists of class VA and class VB. The sample used in this study were all fifth grade students. The sampling technique was randomized groups. Namely class VA as an experimental class using the project method, and class VB as a control class using the guided inquiry method. Based on the results of the analysis of the MANOVA test simultaneously, a significance value of 0.018 < from 0.05 was obtained, so it was said that there was a difference in the effect of the project method and guided inquiry on creative thinking skills and students' cognitive learning outcomes, while partially there was a difference in the effect between the project method and the inquiry method. guided by the creative thinking ability and cognitive learning outcomes of students with p-value p-value 0.164 Pillai's Trace > from a significance level of 0.018, p-value 0.836 Wilks' Lambda and a significant value of 0.018, p-value 0.196 Hotelling's Trace and a significant value of 0.018, p-value 0.196 and 0.018 Roy's Largest Root. The conclusion is that there is a difference in the effect between the project method and guided inquiry on students' creative thinking abilities and cognitive learning outcomes.